Carbapenem-Resistant Klebsiella pneumoniae Associated with COVID-19 - Irina Magdalena Dumitru; Mirela Dumitrascu; Nicoleta Dorina Vlad; Roxana Carmen Cernat; Carmen Ilie-Serban; Aurelia Hangan; Raluca Elena Slujitoru; Aura Gherghina; Corina Mitroi-Maxim; Licdan Curtali; Dalia Sorina Carp; Anca Dumitrescu; et al. (MDPI AG, 2021)
Infections with carbapenem-resistant Enterobacteriaceae are emerging as an important challenge in healthcare settings. Currently, carbapenem-resistant Klebsiella pneumoniae (CRKP) are the species of CRE most commonly encountered in hospitals. CRKP is resistant to almost all available antimicrobial agents, and infections with CRKP have been associated with high rates of morbidity and mortality, particularly among persons with prolonged hospitalization exposed to invasive devices. We report nine patients hospitalized in an intensive care unit (ICU) with severe coronavirus disease 2019 (COVID-19) who developed invasive infections due to carbapenemase-producing Klebsiella pneumoniae (CP-Kp), KPC and OXA-48, strains that have not been previously identified in our hospital. Despite ceftazidime/avibactam therapy, five patients died. Coinfections can contribute to a poor prognosis for patients with COVID-19, especially for high-risk populations such as elderly patients. Therefore, it is crucial to establish a rigorous program of antibiotic administration in intensive care units.